GDP and Productivity Indicators of Albanian Governance, Through Innovations and Knowledge Transfer strategies - Dumi, Alba; Peto, Inilda; Alushaj, Oltjana (Mediterranean Journal of Social Sciences, 2012)
Albania's economy has improved substantially over recent years and has outperformed many other countries in the region.However, it is still considered one of the poorest countries in Europe. According to the Bank of Albania, per capita income was $4,070 in2009, and was expected to reach $4,200 in 2010. According to preliminary data by the World Bank's Poverty Assessment Program,12.4% of the population lived below the poverty line in 2008, marking a considerable improvement from 25.4% in 2002; this decline inpoverty levels was due mainly to higher per capita GDP. The official unemployment rate is 13.52%, with almost 60% of the workforceemployed in the agricultural sector, although the construction and service industries have been expanding recently. Albania is open toforeign investment and increasing FDI is a top priority for the Albanian government. Albania has put in place a liberal foreign investmentregime, including a 10 percent flat corporate and income tax and has taken measures to improve the business climate by streamliningbusiness procedures through e-government reforms. These improvements along with NATO membership and progress toward EUintegration have contributed to the increase in investor interest during the last couple of years. Promising sectors for foreign investorsand include: energy (including alternative energies), mining, transportation, telecommunications, and tourism. Tourism has been boostedsignificantly by ethnic Albanian tourists from throughout the Balkans. GDP is comprised of services, including trade, hotels andrestaurants (21%), transport (5.5%), and communication (4.5%) agriculture (19%); construction (14%); industry (10%) and remittances(9%). The Albanian economy has been partially sheltered from the global financial crisis and the economic downturn. The InternationalMonetary Fund (IMF) projects growth at 3.4% and 3.6% for 2011 and 2012 respectively. A reduction in remittances from Albanianworkers abroad has constrained economic activity, although exports grew in 2010. The country’s geographic position places it at thecrossroads of Western and Eastern Europe. A stable U.S. ally, Albania is a member of NATO, the WTO and is in the process of applyingfor candidate status in the European Union. During the global financial crisis, bank deposits shrank considerably and lower liquiditypushed commercial banks to tighten lending. While current bank deposits have reportedly surpassed pre-crisis levels and bank liquidityhas improved, the demand for credit is still low. In December 2009, the growth rate of loans dropped to 10% from 35% in 2008. The lowdemand for credit continued into 2010, with the growth rate of loans slowing to 9.1% for the first 6 months of 2010. In general, thebanking sector remains viable, well capitalized, and able to further finance the economy, as the ratio of loans to deposits, approximately65%, is still low compared to Western standards.